The hells in the ‘Divine Comedy’ and the frescoes in the scrovegni chapel: : contacts between Dante Alighieri and Giotto di Bondone in the 14th century - Piazza de Melo, Thatiane (2021)
This article aims to demonstrate all the impact that the work “Divina Comédia” written by the author Dante Alighieri had on pictorial productions in the 14th century in Italy. In particular, the painting made by the painter Giotto di Bondone in the Scrovegni chapel in Padua will be covered. To achieve such an objective, the verses of this story will be compared with the images, mainly in the part of the fresco on the theme of the Last Judgment, in which Hell and the characters present in this space are similar to the author's description. Therefore, we will present an overview of these close relations between these artistic segments that conveyed a perspective of culture and mentalities in the medieval period.